International developments in shipping - Gerhard Krause (Intereconomics, 1971)
Looking back at the 5th session, at the spirit of its debates and negotiations and at its results, one could indeed conclude that it reflected more cooperation than the preceding ones. Some of the reasons why this happened may be found in the general development. However, to a great extent it was owed to the personality of the President, Mr. Quartley, the Shipping Commissioner in the Government of Ghana. He had proved his ability to chairing international meetings already in IMCO and elsewhere. He has encouraged cooperation by the members of all groups with the effect that no decision was taken under pressure. The 5th session has therefore been that with the least number of resolutions adopted but one of the most successful.
Keywords: 330; Development Policy